The first species of the spider genus Episinus in Colombia (Araneae, Theridiidae) - Chavari, João Lucas; Brescovit, Antonio D. (Zootaxa, 2014)
The spider family Theridiidae Sundevall, 1833 is currently represented by 121 genera and 2,387 species distributed worldwide (Platnick, 2014), of which 52 genera are recorded in the Neotropical region. The genus Episinus Latreille, 1809 has 57 described species but only 29 (50.8%) are known by both sexes (Platnick, 2014). The type species of the genus, E. truncatus Latreille, 1809, was described from Italy.  The last taxonomic of Episinus from the Neotropical region was made by Levi (1955), who proposed 26 species for this region. Levi (1964; 1967) and Buckup & Marques (1992) increased to 37 the number of Neotropical species. Later, 13 species were removed from Episinus, where seven species were transferred to the genus Neopisinus (Marques et al., 2011) and six species to the genus Janula (Yoshida & Koh, 2011). Currently, 24 species have been recorded from the Neotropical region, almost 40% of the known species in the world.